Lietuvių dvikamienių vardų su pirmuoju dėmeniu vaiš- raidos bruožai - Sinkevičiūtė, Daiva (Baltistica, 2008)
This article investigates changes that took place while writing down the first component vaiš- of compound proper names in various types of documents by people with a varying knowledge of Lithuanian. The following variants of vaiš- are attested, due to phonetic context and incorrect adaptation in a foreign writing system: vais-, vaiz-, vaiž-, vois-, voiš-, voiz-, voiž-, veiš- and veis-. Stems of this type were further abbreviated, giving rise to the component vai- (voi-). This process took place in all Lithuanian-speaking areas, but was especially frequent in the Žemaitian region. It is particularly common among compound proper names with the second component °nor-, rarer with °but-, °vyd-, °vil-. The stem vai- is thus a variant of vaiš- and is not related to Lith. vajóti, vajỹs, as it is often maintained in onomastic literature. Compound proper names with vos- as their first component are probably also should be linked to compound words with vaiš- as their first component. In the process of writing proper names that contain vaiš- in non-Lithuanian documents, [ai] was monophthongized and written instead with or <o>. The process of monophthongization was stimulated by the dialect of the Žemaitian region as well.